Regional astrogliosis in the mouse hypothalamus in response to obesity. Issue 6 (20th February 2013) - Buckman, Laura B.; Thompson, Misty M.; Moreno, Heidi N.; Ellacott, Kate L.J.
Abstract Obesity is associated with chronic low‐grade inflammation in peripheral tissues, which contributes to the development of comorbidities such as insulin resistance and cardiovascular disease. While less extensively characterized, obesity also promotes inflammation in the central nervous system (CNS) and the consequences of this inflammation for CNS function are only beginning to be examined. In response to CNS insults such as inflammation, astrocytes undergo a process of hypertrophy and hyperplasia known as reactive astrogliosis. We used immunohistochemistry to examine the differential distribution of the astrocyte marker glial‐fibrillary acidic protein (GFAP) in the brains of diet‐induced or genetically obese mice compared with their respective lean controls to determine whether different nuclei of the hypothalamus showed comparable astrogliosis in response to obesity. The areas that showed the highest differential GFAP immunoreactivity between lean and obese animals include the medial preoptic, paraventricular, and dorsomedial nuclei. Comparatively, little astrogliosis was seen in the ventromedial nucleus, lateral hypothalamus, or anterior hypothalamic area. In obese animals high levels of GFAP immunoreactivity were often associated with the microvasculature. There were no differences in the differential distribution of GFAP staining between obese animals and their lean controls in the diet‐induced compared with the genetic model of obesity. The exact cause(s) of the astrogliosis in obesity is not known. The finding that obesity causes a distinct pattern of elevated GFAP immunoreactivity associated with microvessels suggests that the astrogliosis may be occurring as a response to changes at the blood–brain barrier and/or in the peripheral circulation. J. Comp. Neurol., 521:1322–1333, 2013. © 2012 Wiley Periodicals, Inc.